New Zealand Labour Market Dynamics: Pre- and Post-global Financial Crisis - Weshah Razzak (New Zealand Government, The Treasury, 2014)
A persistent increase in the unemployment rate ignites speculations about whether the changes to unemployment are structural or cyclical. The New Zealand economy has been through major restructuring since the mid-1980s. The labour market's institutional changes were the last in the sequence of these reforms. As reforms began to take effect and expectations adjusted, unemployment in New Zealand has declined steadily and persistently since 1993-1994. Along the way, however, transitory increases in unemployment occurred. Major increases occurred after the Asian financial crisis and the global financial crisis with similar dynamics.
Keywords: J60; C2; C3; 330; Natural Rate of Unemployment; Speed of adjustment of the New Zealand labour market; estimation; Natürliche Arbeitslosenquote; Beveridge-Kurve; Finanzkrise; Erwerbstätigkeit; Neuseeland